The effect of using the frog virtual learning platform for mathematics education in primary schools / Parameshvaran Varaman, Dr Jeya Amantha Kumar and Siti Nazleen Abdul Rabu - Varaman, Parameshvaran; Kumar, Jeya Amantha; Abdul Rabu, Siti Nazleen (Universiti Teknologi MARA, Kedah, 2023)
Frog VLE was introduced by the Malaysian Ministry of Education, an online-based virtual learning platform that delivers learning content through multimodal methods to assist learning activities. This platform has significantly impacted Malaysian education and has been found to be beneficial as a teaching aid for mathematics, yet not much is known of the effect on primary school education. Therefore, using a quasi-experimental design, this study examines the effect of using the Frog VLE platform for mathematics primary education of year four students in Malaysia. Students were assessed based on mathematical achievement and perception of interest in using the platform, and the findings reflect that most students found the platform and its contents appealing and improved their interest in learning mathematics and enjoyed its benefits. Furthermore, it was observed that students performed better when exposed to the VLE compared to the traditional classroom but lacked confidence in using the platform. These findings can help policymakers consider future methods for using virtual learning platforms to enhance mathematics learning outcomes in Malaysian primary schools.